Bacterial type III effectors inhibit cell lifting by targeting integrin-linked kinase. - Tegtmeyer, Nicole; Backert, Steffen (Cell Host & Microbe, 2009)
Many pathogenic bacteria are able to surmount exfoliation and colonize the host epithelium efficiently. In a recent article in Nature, Kim et al. (2009) show that Shigella flexneri OspE, a conserved type III effector, reinforces host cell adherence and prevents detachment of the infected cells by interacting with integrin-linked kinase.